Pelaksanaan Perda Kabupaten Boyolali Nomor 19 Tahun 2016 Tentang Penyelenggaraan Perparkiran Oleh Dinas Perhubungan - Bayu Purwo Andoko; Nanik Sutarni; Ananda Megha Wiedhar Saputri (Jurnal Bedah Hukum, 2022)
The administration of the state is identical with power based on authority. For example, in the local government environment, namely the authority in the field of transportation for parking matters, which in the Boyolali Regency Government is contained in Local regulations number 19 of 2016 concerning Parking Management, which is carried out by the Department of Transportation. The implementation of good parking is intended to support development and economic growth and ensure safety, smoothness, order, security and comfort. However, in reality there are still parking activities that are not appropriate and interfere with safety, smoothness, order, security, and comfort, both for motorists using road users and pedestrians using sidewalks. The purpose of this study was to determine the implementation of the Regional Regulation on Parking Management and the obstacles faced. This research is a descriptive research with an empirical juridical approach. By collecting primary data by conducting interviews with officials at the Department of Transportation in charge of parking matters, namely the Head of the Operational Supervision and Violation Enforcement Section. Based on the results of the study, it is understood that the implementation of Local regulations number 19 of 2016, which was carried out by the Department of Transportation was followed up by Local regulations of Boyolali Regency number 12 of 2021 concerning Public Service Retribution, Local regulations of Boyolali Regency number 13 of 2021 concerning Business Services Retribution, and Decree of the Head of the Department of Transportation number 189.6/028/4.11/2021 concerning Standard Operating Procedures at the Department of Transportation. For obstacles, there are budget allocations for the completeness of parking officers, the number of employees who are still lacking, as well as facilities for moving vehicles in the form of locks and vehicle cranes and there are still parking activities that are not in accordance with the provisions. Thus, additional budget allocations, additional staff and facilities, as well as strengthening the duties, functions, and roles of the Department of Transportation still need to be improved by the Boyolali Regency Government. Penyelenggaraan negara identik dengan kekuasaan didasarkan wewenang. Contohnya dalam lingkungan pemerintah daerah, yaitu pada kewenangan bidang perhubungan urusan perparkiran yang mana di Pemkab Boyolali tertuang dalam Perda nomor 19 tahun 2016 tentang Penyelenggaraan Perparkiran, yang dilaksanakan oleh Dinas Perhubungan. Penyelenggaraan parkir yang baik dimaksudkan agar menunjang pembangunan dan pertumbuhan ekonomi serta menjamin keselamatan, kelancaran, ketertiban, keamanan, dan kenyamanan. Namun pada kenyataannya masih terdapat kegiatan parkir yang tidak sesuai dan mengganggu keselamatan, kelancaran, ketertiban, keamanan, dan kenyamanan, baik bagi pengendara kendaraan bermotor pengguna jalan maupun pejalan kaki pengguna trotoar. Tujuan penelitian ini untuk mengetahui pelaksanaan Perda Penyelenggaraan Perparkiran dan hambatan yang dihadapi. Penelitian yang dilakukan adalah penelitian deskriptif dengan metode pendekatan yuridis empiris. Dengan pengambilan data primer dengan melakukan wawancara dengan pejabat pada Dinas Perhubungan yang membidangi urusan perparkiran yaitu Kepala Seksi Pengawasan Operasional dan Penindakan Pelanggaran. Berdasarkan hasil penelitian dipahami bahwa pelaksanaan Perda nomor 19 tahun 2016, yang dilaksanakan oleh Dinas Perhubungan ditindaklanjuti dengan Perda Kabupaten Boyolali nomor 12 tahun 2021 tentang Retribusi Jasa Umum, Perda Kabupaten Boyolali nomor 13 tahun 2021 tentang Retribusi Jasa Usaha, dan Surat Keputusan Kepala Dinas Perhubungan nomor 189.6/028/4.11/2021 tentang Standar Operasional Prosedur pada Dinas Perhubungan. Untuk hambatan terdapat pada alokasi anggaran untuk kelengkapan petugas parkir, jumlah pegawai yang masih kurang, maupun sarana untuk pemindahan kendaraan yang berupa gembok dan derek kendaraan serta masih ada kegiatan parkir yang tidak sesuai ketentuan. Dengan demikian, penambahan alokasi anggaran, penambahan pegawai, dan sarana, serta penguatan tugas, fungsi, dan peran Dinas Perhubungan masih perlu ditingkatkan oleh Pemerintah Kabupaten Boyolali.